The genus Tarsonemus Canestrini and Fanzago, 1876 (Acari: Heterostigmatina: Tarsonemidae) in East Azerbaijan, Iran, with a description of T. lenticulatus sp. nov. and re-description of T. annotatus Livshits, Mitrofanov and Sharonov, 1979 - Gheblealivand, Saeide S.; Irani-Nejad, Karim Haddad; Magowski, Wojciech Ł.; Manzari, Shahab (Zootaxa, 2018)
The tarsonemid mites from soil and plants were explored in a faunistic study of East Azerbaijan province, Northwestern Iran. Our investigation revealed 22 species of the genus Tarsonemus Canestrini and Fanzago, 1876, and its nominative subgenus, including Tarsonemus lenticulatus sp. nov., which is described and illustrated herewith. New records for the fauna of Asia are: Tarsonemus bognari Nemestothy and Mahunka, 1981, T. oncodes Kaliszewski, 1993, T. ravus Kaliszewski, 1993, T. saccatus Livshitz, Mitrofanov and Sharonov, 1979, T. scharschmidti Mahunka, 1970, T. varsoviensis Kaliszewski, 1993 and T. violae Schaarschmidt, 1960. New records for the mite fauna of Western Asia are: Tarsonemus bifurcatus Schaarschmidt, 1959, T. floricolus Canestrini and Fanzago, 1876, T. lacustris Schaarschmidt, 1959, and T. virgineus Suski, 1969; and T. stammeri Schaarschmidt, 1959 is newly recorded from Iran. Re-description and illustrations of Tarsonemus annotatus Livshits, Mitrofanov and Sharonov, 1979 are provided. The incidence of all species found across the examined area and substrates is briefly discussed. A key to females of the genus Tarsonemus in East Azerbaijan is provided.